FAKTOR – FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA PEMERINTAH DAERAH TANJUNG JABUNG BARAT DENGAN ADMINISTARASI SEBAGAI VARIABEL MODERASI - Tanjung, Ferri Saputra; Achyat Budianto; Lubis, Puteri Anggi (Politeknik Negeri Ambon, 2022)
This study aims to determine the effect of planning, human resources and budget execution on budget absorption with administration as a moderating variable in Tanjung Jabung Barat Regency. The samples in this study were the Budget User Authority (KPA), Commitment Making Officer (PPK), Expenditure Treasurer (BP), Financial Administration Officer (PPK), and Paying Order Signing Officer (PPSPM) in the Tanjung Jabung Barat Regency government which were collected 134 respondents. The data in this study are primary data. Hypothesis testing using multiple linear regression analysis and MRA with the help of the SPSS program. The results of research on planning, human resources and budget execution partially on budget absorption. Administration as a moderating variable succeeded in moderating the relationship between planning, human resources and budget execution on budget absorption.